Trans‐apical systemic tricuspid valve‐in‐ring replacement. Issue 6 (18th December 2018) - Ghobrial, Joanna; Reemtsen, Brian; Levi, Daniel S.; Aboulhosn, Jamil
Abstract: Transcatheter valve replacement offers a safe and effective alternative to traditional surgical techniques in patients with congenital heart disease, especially those at high surgical risk. The most common causes of morbidity and mortality in patients with D‐transposition of the great arteries status post Senning or Mustard repair is severe tricuspid valve (TV) regurgitation. Replacement of the systemic TV may be useful in those without severe systemic ventricular dysfunction. We present a case of a patient with D‐loop transposition of the great arteries status post Mustard repair and TV ring placement with subsequent severe systemic TV regurgitation, at high surgical risk, who underwent a transcatheter valve replacement via a trans‐apical approach using an Edwards Sapien XT valve.